2000
DOI: 10.1093/rheumatology/39.2.122
|View full text |Cite
|
Sign up to set email alerts
|

The links between joint damage and disability in rheumatoid arthritis

Abstract: Joint damage progresses constantly over the first 20 yr of RA. It accounts for approximately 25% of disability in established RA. The link between damage and disability is strongest in late (>8 yr) RA. However, avoiding or reducing joint damage in both early and established/late RA is likely to maintain function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
232
2
19

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(264 citation statements)
references
References 45 publications
11
232
2
19
Order By: Relevance
“…In the early stages of RA, functional disability is largely determined by disease activity, while during later stages it is increasingly dominated by the progression of joint deformity and structural bone damage (32)(33)(34)(35). The results of another large trial of MTX and infliximab therapy (Anti-Tumor Necrosis Factor Trial in Rheumatoid Arthritis with Concomitant Therapy; ATTRACT) showed that unemployment at baseline was highly correlated with the level of physical dysfunction (29).…”
Section: Discussionmentioning
confidence: 99%
“…In the early stages of RA, functional disability is largely determined by disease activity, while during later stages it is increasingly dominated by the progression of joint deformity and structural bone damage (32)(33)(34)(35). The results of another large trial of MTX and infliximab therapy (Anti-Tumor Necrosis Factor Trial in Rheumatoid Arthritis with Concomitant Therapy; ATTRACT) showed that unemployment at baseline was highly correlated with the level of physical dysfunction (29).…”
Section: Discussionmentioning
confidence: 99%
“…In early RA, radiographic status is not related to functional outcome measures such as the Health Assessment Questionnaire (13) score, and in established disease (duration 5-8 years) changes visualized by radiography explain only ϳ25% of disability in patients with established RA (14). It appears likely that the more detailed information provided by MRI could capture disease manifestations responsible for a higher proportion of patient disability.…”
Section: Discussionmentioning
confidence: 99%
“…A DAS28 nonresponse was defined as an improvement of Ͻ0.6 points or a final DAS28 score of Ͼ5.1 points. Patients achieving clinical remission at 6 months were identified according to EULAR criteria (DAS28 Ͻ2.6 points) (38). In addition, the patient's global assessment of his or her overall health was recorded at each visit, using a visual analog scale of 0-100 mm, where 0 ϭ best and 100 ϭ worst.…”
Section: Methodsmentioning
confidence: 99%